2012
DOI: 10.5267/j.msl.2012.06.043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of informal communication on the leadership styles in governmental organizations

Abstract: These days, it is not possible to accomplish tasks without having productive relationships with the rest of the world. Although there are some evidences, which indicate informal organizations normally face some limitations on their return but there are also some studies suggesting that informal organizations are the best ways for making significant changes. Recently, many people have suggested that informal organizations provide good infrastructures for organization's workflow many conflict of interests could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The reported that there was no meaningful relationship between leadership style and gender, leadership style and job experience, organizational change and gender, management change and gender. Sehhat et al (2012) investigated the relationship between informal communications with leadership style in some of governmental organizations located in free islands of Chabahar, in south east part of Iran. They reported that there was a positive and meaningful relationship between leadership style and informal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The reported that there was no meaningful relationship between leadership style and gender, leadership style and job experience, organizational change and gender, management change and gender. Sehhat et al (2012) investigated the relationship between informal communications with leadership style in some of governmental organizations located in free islands of Chabahar, in south east part of Iran. They reported that there was a positive and meaningful relationship between leadership style and informal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…(Ehigie & Akpan, 2004). Sehhat et al (2012) studied the relationship between informal communications with leadership style in Iran and reported that there was a positive and meaningful relationship between leadership style and informal relationships. Moghaddas Pour et al (2012) studied the relationship between relationship-oriented leadership style and solution-oriented strategy as well as between leadership style and conflict management.…”
Section: Introductionmentioning
confidence: 99%